Pengembangan Media Tiga Dimensi Diorama Dalam Materi Ekosistem Di Sekolah Dasar - Sapitri, Mukti Gebi; Sumardi, Sumardi (Universitas Pakuan, 2025)
This study aims to develop and create a new interesting and interactive learning method used in Natural Sciences and Social Sciences (IPAS) subjects. The purpose of this study is to teach fifth grade elementary school students about the material about ecosystems through three-dimensional dioramas. As a result, students are not actively involved in class and do not understand the material being taught. According to this study, the diorama uses a research and development method that uses the ADDIE development model approach, which includes the steps of analysis, design, development, implementation, and evaluation. After that, three experts in material, language, and learning media validated the media products that had been created. The results showed that the material component scored 86% with a valid category, and the language and material components scored 64% with a valid category.